2023
DOI: 10.3390/w15132392
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Adsorption Conditions Using Response Surface Methodology for Tetracycline Removal by MnFe2O4/Multi-Wall Carbon Nanotubes

Abstract: In this study, the optimal conditions and effects of external factors on tetracycline adsorption by magnetic multi-walled carbon nanotubes (MMWCNTs) were established by a response surface methodology for the first time. Batch adsorption experiments showed that increasing the dosage and contact time effectively promoted the adsorption of tetracycline and maximum removal of 97.93–99.13% was achieved at pH 3–7. The pseudo-second-order model and Fourier-transform infrared spectroscopy spectra indicated that the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Also, the preheating temperature influences rising UTS according to the major effects plot, the maximum UTS is reached at the highest peak of 550 °C and 5 %. B 4 C– ZrO 2 reinforced ceramics particles [ 38 , 52 ]. The interplay of temperature and volume fraction impacts the UTS of the materials as shown in the Contour 2D Plot of UTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the preheating temperature influences rising UTS according to the major effects plot, the maximum UTS is reached at the highest peak of 550 °C and 5 %. B 4 C– ZrO 2 reinforced ceramics particles [ 38 , 52 ]. The interplay of temperature and volume fraction impacts the UTS of the materials as shown in the Contour 2D Plot of UTS.…”
Section: Resultsmentioning
confidence: 99%
“… Where n is the number of data , the predicted and measured values and m data points. The mean absolute error (MAE) is used to calculate the lowest error from the predicted model and expressed in Eq (4) [ 38 ]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, it cannot be ignored that the biosorption and removal efficiency of algae on heavy metal ions may be relevant to multiple factors, such as pH, temperature, algal biomass, and ionic concentration. As one of the most commonly used response surface methods (RSM), Box–Behnken design (BBD) is ideal for seeking the optimal conditions of adsorption process ( Moon et al, 2013 ; Mutalik et al, 2021 ; Pascual et al, 2022 ; Ramesh et al, 2023 ; Zhao et al, 2023 ). For instance, Zeng et al (2022) reported that the peak adsorption of Microcystis aeruginosa powder on Cu 2+ , Cd 2+ , and Ni + was 83.24, 92.00, and 88.67% under the initial concentration of Cu 2+ , Cd 2+ , and Ni + of 25 mg/L, 5 mg/L,and 15 mg/L, the temperature of 30°C, 35°C, pH value of 8, 8, and 7, and the adsorption time of 5 h, 4 h, and 1 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the optimal temperature range of bioremediation is narrow due to the fact that the biosorption process is endothermic and the removal efficiency enhanced along with the increase in temperature. However, high temperature may destroy cell structure and some active sites, lowering the removal rate ( Zhao et al, 2023 ). Therefore, in the practical settings, D. salina cells can be domesticated to grow at pH of 5–6 and temperature of 25–30°C to adsorp the heavy metals from the wastewater, achieving a higher removal efficiency of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…RSM is one of the important experimental planning methodologies of design of experiments (DoE) [34]. RSM's primary benefit lies in its efficacy, allowing for limited experimental runs to forecast factor interactions and obtain optimal conditions with precision [23].…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%